Transferência de tecnologia agropecuária: o dificil dilema da formação extensionista - Guedes, Maria Eliza Correa (1996)
The objective of this paper was the analysis of the training process of extensionists adopted by EMA TER/DF, in order to verify which basic factors need to be improved to maintain a team of extensionists with good tec1mical skill and with the capability of facings, more and more complex situation in a highly changeable environrnent. These solutions depends on a high leveI of knowledge and training. The study was developed during 1995 with the objective of collecting enough information for a better comprehension of the subject. In addition to the bibliographical and literature search, field research was undertake among 30 extensionists from EMATER/DF. The results obtained were divided according four fundamental points of view: the mechanistic sight of the world the role of tec1mology; the need of specialisation: and the methodology of nlral extension. At the same time was determined that training of extensionists should notfollow to the same ritualistic, conservative and predetermined character that has being used until now.